Research on the influence of LPG/CNG injector outlet nozzle diameter on uneven fuel dosage - Szpica, Dariusz (Transport, 2018)
The paper presents an original flow research methodology in LPG/CNG injectors. When adapting alternative LPG systems of the IV generation, very often the injector nozzles are adapted individually to change the flow parameters. Hence, in the paper the author attempted to evaluate the influence of the injector nozzle diameter (min and max) on the uneven fuel dosage. The determined average throughputs were 0.0235–3.3683 mm2. The averaged difference in the unevenness reached 0.0419%, its minimum value is 0.0694 and the maximum is 0.7703, which can influence the correction of the mixture composition made through the oxygen sensor. Additionally, the flow characteristics of the injectors for both diameter variants have been presented, showing the necessity of inspecting the component after nozzle boring.First published online 29 March 2016